THE RELATION BETWEEN EMOTIONAL INTELLIGENCE AND CARING BEHAVIOR IN NURSING STUDENTS OF STIKES MEDISTRA INDONESIA - Rizqon Nur Fajrian; I Ratnah; Lina Indrawati (Rena Cipta Mandiri, 2024)
Caring is an attitude, action or behavior carried out by nurses with the aim of giving feelings of emotional and physical security to others sincerely without discriminating against patients. Caring for nurses is a benchmark for patient satisfaction and also the quality of nursing services. caring behavior is not inherited or hereditary, but can be trained and developed since sitting in lectures. This caring behavior is also influenced by several factors, one of which is a person's Emotional Intelligence. Emotional Intelligence has several elements in common with the components in Caring. This research uses descriptive correlation method which is quantitative and cross sectional research design. The population in this study were nursing students from 2018 to 2022, totaling 276 students. The research sample was based on the slovin formula as many as 163 respondents were taken using Probability Sampling type stratified sampling. The research shows that there is a relationship between emotional intelligence and caring behavior of nursing students (P value = 0.000) which means that there is a significant positive relationship between emotional intelligence and caring behavior in nursing students. So suggestions for further researchers to examine other things that affect emotional intelligence and caring behavior as well as ways to keep nursing students in caring behavior. Keyword : Caring, emotional intelligent, student.